Breaking Gender Myths: Analyzing Employee Performance in a West Java Beverage Company - Fitriatu Lam'ah; Ahman, Eeng; Rofaida, Rofi (Buana Gender: Jurnal Studi Gender dan Anak, 2023)
Employee performance is an important determinant for the company. The company's ability to achieve goals, one of which is influenced by the performance of its employees. Employee performance in a company varies. Many companies whose employees are dominated by men, because argue that men have better performance than women. However, many studies explain that employee performance is not influenced by gender. This study aims to analyze employee performance in relation to gender. The research was conducted at a packaged beverage company in West Java. The sample of this research is 258 people from the company. Research using quantitative methods with descriptive analysis. Data obtained through literature studies and questionnaires. From the research results it is known that men and women have the same performance. Even if seen from the score, women outperformed men. Thus, companies must provide equal opportunities for men and women to work. Keywords: Employee performance, gender, men, women